Quantification of Plasmodium ex vivo drug susceptibility by flow cytometry - Wirjanata, Grennady (Malar J, 2015)
BACKGROUND: The emergence and spread of multidrug-resistant Plasmodium falciparum and Plasmodium vivax highlights the need for objective measures of ex vivo drug susceptibility. Flow cytometry (FC) has potential to provide a robust and rapid quantification of ex vivo parasite growth. METHODS: Field isolates from Papua, Indonesia, underwent ex vivo drug susceptibility testing against chloroquine, amodiaquine, piperaquine, mefloquine, and artesunate. A single nucleic acid stain (i.e., hydroethidine (HE) for P. falciparum and SYBR Green I (SG) for P. vivax) was used to quantify infected red blood cells by FC-based signal detection. Data derived by FC were compared to standard quantification by light microscopy (LM). A subset of isolates was used to compare single and double staining techniques. RESULTS: In total, 57 P. falciparum and 23 P. vivax field isolates were collected for ex vivo drug susceptibility testing. Reliable paired data between LM and FC was obtained for 88 % (295/334) of these assays. The median difference of derived IC(50) values varied from −5.4 to 6.1 nM, associated with 0.83–1.23 fold change in IC(50) values between LM and FC. In 15 assays (5.1 %), the derived difference of IC(50) estimates was beyond the 95 % limits of agreement; in eleven assays (3.7 %), this was attributable to low parasite growth (final schizont count < 40 %), and in four assays (1.4 %) due to low initial parasitaemia at the start of assay (<2000 µl(−1)). In a subset of seven samples, LM, single and double staining FC techniques generated similar IC(50) values. CONCLUSIONS: A single staining FC-based assay using a portable cytometer provides a simple, fast and versatile platform for field surveillance of ex vivo drug susceptibility in clinical P. falciparum and P. vivax isolates.